Współczesne koncepcje amerykańskie w dziedzinie wyboru prawa właściwego na przykładzie zobowiązań deliktowych (przegląd doktryny i orzecznictwa) - Sokołowski, Marek (Wydział Prawa i Administracji UAM, 1980)
The aim of this article is to discuss some of the new approaches to the choice of law problem which have been recently developed in the United States and to show their impact on the case law of multistate torts. Discussing the reasons for the retreat from Restatement I, the author indicates the inefficiency of the dogmatic treatment of the more and more complex social and economic relations of our times. The abandonment of the hard-and-fast choice-of-law rules was also helped by the ''common law courts' distrust for the too broad and all-encompasising rules of continental origin. It seems that the retreat from Restatement I was made directly possible by the development of the local law theory which has abolished the basic elements of the logical scheme of the vested rights theory (superlaw, original jurisdiction, territorialism etc). Searching for new criteria, representatives of the new theory suggest consideration of teleological (policy) factors in choosing the proper law. In the 1960's courts, following directives of the new doctrine, ceased to apply the lex loci delicti rule in favor of the directive providing for the application of the law of the state of the most significant relationship to the matter under consideration. Anticipating the threat of unpredictability and non uniformity of results, the adherents of the new approach stated that those traditional policies were of no importance in torts and should be subordinated to the proper objective of the conflicts law i. e. the achievement of just and fair results (Babcock). However, the analysis of the post Babcok case law development in New York, as well as in other states following New York experiments, justifies the statement that the policy of uniformity and predictability cannot be seperated from policies favoring justice and fairness. Hence, the visible departure from the ad chasm approach in New York case law. Worth noticing here are Judge Fuld's rules adopted by the majority in the well known 'Neumeier' case. Considering the range of connecting factors, the said rules can hardly be classified as revolutionary. Their novelty lies in their narrowness i. e. the fact that they were formulated for the disposition of solely 'guest-statutes' cases. It seems that the tendency to formulate a great number of rules that are each directed to a relatively narrow situation will finally prevail in the case law of the U.S. The last part of the article is devoted to the discussion of selected new doctrinal approaches, namely those accepted by Restatement II as well as by B. Currie and A. Ehrenzweig. It is indicated that, in spite of their common functional background, the authors differ in such foundamental matters as the identification of the state whose policy should be given priority, methods for the determination of state's interestes, methods of resolving true policy conflicts etc. Moreover, no agreement has been so far reached as to the definition of the central notion of purpose of law' and the criteria for its determination. The above mentioned faults of the new theories have mainly contributed to the rejection of ad chasm approach. The theories discussed in this paper can be also criticized form the methodological point of view. B. Currie, for instance, looking for the positive justification of his conclusions, analyses the U.S. Supreme Court's decisions concerning workmen's compensation. It seems that this is too narow a basis upon which to build general conclusions concerning choice of law problems. The same refers to Restatement II. Solutions accepted there are based mainly On the analysis of the New York 'guest statutes cases'.
Contemporary American Concepts in the Sphere of Proper Rights Exemplified by Delict Recognizance (Review of Doctrines and Jurisdiction)
Keywords: WPiA